Characterization and Repeat Analysis of the Compact Genome of the Freshwater Pufferfish Tetraodon nigroviridis - Crollius, H. Roest; Jaillon, O.; Dasilva, C.; Ozouf-Costaz, C.; Fizames, C.; Fischer, C.; Bouneau, L.; Billault, A.; Quetier, F.; Saurin, W.; Bernot, A.; Weissenbach, J. (Genome Research, 2000)
Tetraodon nigroviridis is a freshwater pufferfish 20–30 million years distant from Fugu rubripes. The genome of both tetraodontiforms is compact, mostly because intergenic and intronic sequences are reduced in size compared to other vertebrate genomes. The previously uncharacterized Tetraodon genome is described here together with a detailed analysis of its repeat content and organization. We report the sequencing of 46 megabases of bacterial artificial chromosome (BAC) end sequences, which represents a random DNA sample equivalent to 13% of the genome. The sequence and location of rRNA gene clusters, centromeric and subtelocentric satellite sequences have been determined. Minisatellites and microsatellites have been cataloged and notable differences were observed in comparison with microsatellites from Fugu. The genome contains homologies to all known families of transposable elements, including Ty3-gypsy, Ty1-copia, Line retrotransposons, DNA transposons, and retroviruses, although their overall abundance is <1%. This structural analysis is an important prerequisite to sequencing the Tetraodongenome.[The sequence data described in this paper have been submitted to the EMBL data library under accession nos.AJ245809, AJ270048, AJ245808, AJ270029–AJ270047, DS42722 andAL305790–AL352938.]
10.1101/gr.10.7.939